Half the Perfect World: Writers, Dreamers and Drifters on Hydra, 1955-1964 - Genoni, Paul; Dalziell, Tanya (Monash University Publishing, 2018)
Half the Perfect World tells the story of the post-war international artist community that formed on the Greek island of Hydra, which centred on Australian writers George Johnston and Charmian, and included Canadian poet, novelist and songwriter, Leonard Cohen.